(3GdeZfj aj GdCUhds - (3GdNHGRj , YeQ Hf eMeO Hf YeQ GdNLfOj, LdGd GdOjf CHh eMeO,J (B691 (3g` s
(3ChdgG (B:s
(3hdG jJhba MbjbJg Ydi EQGOI GdaYd ef GdCeQ YfOfG NdGakG ddeYJRdI s
(3BNQgG (B:s
(3aYfO JYPQ GdXQa HUjQ cJGfI Yf GdTQW eLGRkG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B315s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1749s
Keywords: (3CUhd Gdabgs